2000
DOI: 10.1021/es001068h
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Arsenite by Dissimilatory Reduction of Adsorbed Arsenate

Abstract: Sulfurospirillum barnesii is capable of anaerobic growth using ferric iron or arsenate as electron acceptors. Cell suspensions of S. barnesii were able to reduce arsenate to arsenite when the former oxyanion was dissolved in solution, or when it was adsorbed onto the surface of ferrihydrite, a common soil mineral, by a variety of mechanisms (e.g., coprecipitation, presorption). Reduction of Fe(III) in ferrihydrite to soluble Fe(II) also occurred, but dissolution of ferrihydrite was not required in order for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
233
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(249 citation statements)
references
References 36 publications
12
233
1
3
Order By: Relevance
“…7 and 8). Masscheleyn et al (1991) and Zobrist et al (2000) reported from laboratory experiments that under reducing conditions part of As bound to Fe-oxyhydroxides was released before Fe implying reductive desorption from Fe-oxyhydroxides rather than reductive dissolution. Therefore, the shallow release of As in the sediments of Lake Shirokoe and Lake Yamsovey is attributed to both reductive desorption from Fe-oxyhydroxides and mobilization from OM upon oxidation.…”
Section: Arsenic and Antimonymentioning
confidence: 99%
“…7 and 8). Masscheleyn et al (1991) and Zobrist et al (2000) reported from laboratory experiments that under reducing conditions part of As bound to Fe-oxyhydroxides was released before Fe implying reductive desorption from Fe-oxyhydroxides rather than reductive dissolution. Therefore, the shallow release of As in the sediments of Lake Shirokoe and Lake Yamsovey is attributed to both reductive desorption from Fe-oxyhydroxides and mobilization from OM upon oxidation.…”
Section: Arsenic and Antimonymentioning
confidence: 99%
“…Dissimilatory arsenate reduction has been reported in lab cultures using granular anaerobic digester sludge and an alumina based ABSR (16). The dissimilatory reduction and mobilization of arsenic specifically adsorbed onto the surface of ferrihydrite has also been studied (17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…4), As is probably not only released due to the reduction of Fe and Mn oxides and subsequent release of associated As. The reduction of As(V) to As(III), as suggested by Zobrist et al, 21 probably also plays a significant role when sufficiently low redox potentials are being reached on day 90. This should, however, still be confirmed in future experiments.…”
Section: Relation Betweenmentioning
confidence: 87%
“…The accumulation of IC also indicates the establishment of reducing conditions regardless the presence of Fe or Mn oxide reduction. These reducing conditions might involve the reduction of As(V) to As(III) and subsequent As release which was not a result of Fe or Mn oxide reduction, as suggested by Zobrist et al 21 The fact that the correlation between As and IC is closer compared to the correlation between As and TOC moreover illustrates that the establishment of these reducing conditions is more important for As mobilisation compared to the association of As with soluble organic material. Sisr et al 44 indeed also previously observed that the addition of organic manure does not affect the leaching of As from soil in a column experiment.…”
Section: Relation Betweenmentioning
confidence: 88%